2003
DOI: 10.1097/01.sla.0000072111.53797.44
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel In Vitro Human Tissue-Based Angiogenesis Assay to Evaluate the Effect of Antiangiogenic Drugs

Abstract: Epothilone B may be an effective antiangiogenic agent in a variety of tumor types. The authors speculate that this in vitro model might provide useful information to the clinician on the effect of specific antiangiogenic agents on individual tumors. This may be particularly useful in patients with tumors that, as a group, are unresponsive to treatment with antineoplastic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…Additionally, as a tubulin-binding agent, patupilone should show antivascular effects by disrupting rapidly proliferating and immature endothelial cells, which have a particularly strong dependence on tubulin to maintain their shape (9). Support for this hypothesis was recently provided with cultured cells using low doses of patupilone (10) and on clinical tumor explants (11). Inhibition of endothelial cell function could also have a negative effect on the metastatic process.…”
mentioning
confidence: 84%
“…Additionally, as a tubulin-binding agent, patupilone should show antivascular effects by disrupting rapidly proliferating and immature endothelial cells, which have a particularly strong dependence on tubulin to maintain their shape (9). Support for this hypothesis was recently provided with cultured cells using low doses of patupilone (10) and on clinical tumor explants (11). Inhibition of endothelial cell function could also have a negative effect on the metastatic process.…”
mentioning
confidence: 84%
“…Epothilone B has been described to have superior potency to paclitaxel in inhibition of endothelial cell proliferation in vitro after continuous low-dose administration (9). Woltering et al (8) have reported that epothilone B inhibits in vitro angiogenesis at relatively high concentrations. Both observations do not provide insight in angiogenesis inhibition at subtoxic concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Epothilones are structurally unrelated to taxanes but share their ability to stabilize microtubules (7). Evidence for antiangiogenic properties of epothilone B has been provided by the observation that vessel formation was inhibited in vitro (8) and by studies on frequent low-dose administration, which resulted in inhibition of proliferation of endothelial cells in culture (9). Vinca alkaloids show a different mode of action than taxanes and epothilones: they inhibit both tubulin polymerization and mitotic spindle formation.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin and turmeric extracts were assayed for antiangiogenic activity in a human placental vein disc angiogenesis model (HPVAM) developed by Woltering et al (2003). The test compounds were dissolved in culture media and used human placental vein assay in 96-well plates based on the methods described previously (Hornick et al, 2003;Liu et al, 2005).…”
Section: In Vitro Human Tissue-based Angiogenesis Assaymentioning
confidence: 99%